Strategies Used by Middle Managers to Support Employees Carrying Out Emotionally Demanding Work: Which Strategies and Why Those Ones? - Pelletier-Bosshard, Emma; Freeman, Andrew; Jauvin, Nathalie; Côté, Nancy (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2021)
Many areas of practice in health and social services are emotionally demanding. This type of work can be associated with psychological health problems and middle managers play a key role in reducing such risks for their staff. Although the importance of providing this support is recognized, attaining such an objective is not necessarily straightforward because of the multiple demands that managers must juggle.Using an ergonomic perspective, this qualitative research study, which was conducted in a regional child protection service in Quebec (Canada), aimed to identify the strategies used by middle managers to support staff whose work is considered emotionally demanding. The results reveal that managers use a range of support strategies, which fall into seven categories. Although the strategies are distributed along two axes, proximity (direct, indirect) and time (short-term, long-term), they tend to be more direct and short-term (e.g., provide emotional support). The choice of strategies is influenced by various facilitating or constraining organizational, interpersonal and individual factors. A strong influence appears to be time availability.This study provides a detailed picture of the strategies used by middle man-agers and the complexity with which these individuals are confronted in providing their staff with support. Further research is required, for example, to better understand the impact of certain factors on the choice of support strategies and to evaluate the impact of support strategies from a staff perspective.